Length-weight relationship and cluster analysis in puntius bulu: applications in fisheries management - Andri Hendrizal; Muhammad Fauzi (Institute of Computer Science (IOCS), 2023)
This study aimed to explore the relationship between the length and weight of Subhan fish (Puntius bulu) and to identify cluster structure in populations based on various variables. Descriptive and exploratory analyses were performed on 51 fish samples measured for total length, raw length, total weight, total gonadal weight, sex, and gonad maturity level. The relationship between fish length and weight was found to be strong, reflecting growth patterns common in many fish species. In addition, cluster analysis revealed the presence of two distinct groups of fish in the population, which may reflect differences in life cycle stages, environmental conditions, or life strategies. These results have significant implications in fisheries management, including stock assessment, capture planning, and conservation.